Inoculation of sugarcane with diazotrophic bacteria - Schultz,Nivaldo (2014)
The sugarcane industry, a strategic crop in Brazil, requires technological improvements in production efficiency to increase the crop energy balance. Among the various currently studied alternatives, inoculation with diazotrophic bacteria proved to be a technology with great potential. In this context, the efficiency of a mixture of bacterial inoculant was evaluated with regard to the agronomic performance and N nutrition of sugarcane. The experiment was carried out on an experimental field of Embrapa Agrobiologia, in Seropédica, Rio de Janeiro, using a randomized block, 2 × 3 factorial design (two varieties and three treatments) with four replications, totaling 24 plots. The varieties RB867515 and RB72454 were tested in treatments consisting of: inoculation with diazotrophic bacteria, N-fertilized control with 120 kg ha-1 N and absolute control (no inoculation and no N fertilizer). The inoculum was composed of five strains of five diazotrophic species. The yield, dry matter accumulation, total N in the shoot dry matter and the contribution of N by biological fixation were evaluated, using the natural 15N abundance in non-inoculated sugarcane as reference. The bacterial inoculant increased the stalk yield of variety RB72454 similarly to fertilization with 120 kg ha-1 N in the harvests of plant-cane and first ratoon crops, however the contribution of biological N fixation was unchanged by inoculation, indicating that the benefits of the inoculant in sugarcane may have resulted from plant growth promotion.